Policy Conflict: Women's Groups and Institutionalized Restorative Justice. (February 2015) - Nelund, Amanda
The Nova Scotia Restorative Justice (NSRJ) program is a province wide, systemic juvenile restorative justice program in Nova Scotia. This program offers restorative justice intervention, at varying points in the criminal justice process, for all crimes except sexual assault and intimate partner violence. This study, a case study of the policy process, reveals that this exception is not based on restorative justice (RJ) theory but instead reflects local political struggles. This case reminds policy makers that they must consider local context and stakeholders when crafting RJ programming.